The cost of equity in Canada: An international comparison - Jonathan Witmer (Bank of Canada, 2008)
This paper calculates an implied cost of equity for 19 developed countries from 1991 to 2006. During this period, there has been a decline in the cost of equity of about 10-15 bps per year, which can be partially attributed to declining government yields and declining inflation. Analyst forecast inaccuracy, a proxy for firm-level earnings opacity, is positively related to the cost of equity. If this variable captures differences in disclosure across firms, then improvements in disclosure regulation may benefit firms by lowering their cost of equity. I also include countrylevel variables that measure disclosure requirements, director liability, and the ability for shareholders to sue directors. Higher levels of these measures are associated with a lower cost of equity. Previous studies [e.g., Hail and Leuz (2006a)] have found a similar relation, but my study is unique in that it uses a different measure of investor protection, which may better reflect regulatory differences across countries, and it shows this relation holds for developed countries. After controlling for the characteristics of firms that analysts choose to cover in each country, differences in the properties of analyst forecasts across countries, and differences in accounting standards across countries, Canada's cost of equity is statistically different from a handful of countries and is about 20 to 40 bps higher than that of the United States. Lowering Canadian firms' cost of equity by this amount would have large economic benefits given the size of Canada's capital markets.
Keywords: G30; G38; 330; Financial markets; International topics; Unternehmensfinanzierung; Eigenkapital; Kosten; Wettbewerb; Industriestaaten; Kanada